2008
DOI: 10.1093/nar/gkn528
|View full text |Cite
|
Sign up to set email alerts
|

DNA base flipping by both members of the PspGI restriction-modification system

Abstract: The PspGI restriction–modification system recognizes the sequence CCWGG. R.PspGI cuts DNA before the first C in the cognate sequence and M.PspGI is thought to methylate N4 of one of the cytosines in the sequence. M.PspGI enhances fluorescence of 2-aminopurine in DNA if it replaces the second C in the sequence, while R.PspGI enhances fluorescence when the fluorophore replaces adenine in the central base pair. This strongly suggests that the methyltransferase flips the second C in the recognition sequence, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…With regard to HP0593 MTase, metal ions are not essential for enzyme activity but stimulate the reaction. Addition of Ca 2+ or Mg 2+ , but not Mn 2+ , Co 2+ or Cd 2+ to the reaction buffer stimulated the activity of the PspGI MTase [56]. Recently, Chan et al, [57] demonstrated that in case of HpyAV restriction endonuclease from H. pylori , activity was stimulated by Mn 2+ and Co 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…With regard to HP0593 MTase, metal ions are not essential for enzyme activity but stimulate the reaction. Addition of Ca 2+ or Mg 2+ , but not Mn 2+ , Co 2+ or Cd 2+ to the reaction buffer stimulated the activity of the PspGI MTase [56]. Recently, Chan et al, [57] demonstrated that in case of HpyAV restriction endonuclease from H. pylori , activity was stimulated by Mn 2+ and Co 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The complete rotation of a nucleotide from the DNA duplex, around the phosphate backbone, and into the catalytic pocket of an enzyme is commonly known as nucleotide flipping. It was first observed for the methyltransferase enzyme HhaI ( 1 ) and has since been observed in many other DNA methyltransferase systems ( 2–6 ) and several DNA-repair enzyme complexes ( 7 , 8 ). Recently, it was demonstrated that the Ecl18kI restriction enzyme uses nucleotide flipping as part of its DNA recognition mechanism ( 9 ).…”
Section: Introductionmentioning
confidence: 95%
“…This report was the first example of an enzyme using nucleotide flipping in a situation where the flipped base is not the target of some chemical modification by the enzyme. This seemed a surprising and energetically extravagant method for recognizing a short-DNA sequence, but was soon found to apply to the evolutionarily related enzymes, PspGI ( 6 , 10–14 ) and EcoRII-C ( 11 , 15 ) the catalytic subunit of EcoRII ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Significant sequence similarity between Ecl18kI and PspGI/EcoRII suggests that these enzymes should also flip the nucleotide at the center of the CCXGG sequence, when X is adenine or thymine, and might or might not flip it when X is guanine or cytosine. Direct biochemical evidence for adenine or thymine flipping by PspGI/EcoRII is difficult to provide, but fluorescence experiments with 2-aminopurine (2AP) demonstrate that this adenine analog (which shares some hydrogen bonding requirements with guanine) can be flipped by PspGI/EcoRII ( 12 , 13 ). Evidence for flipping of a natural base in the CCNGG context by PspGI has been obtained for cytosine: this base in the central position of the CCNGG sequence was found to deaminate faster in the presence of the enzyme ( 14 ).…”
Section: Introductionmentioning
confidence: 99%